Increased Androgen Receptor and Remodeling in the Prostatic Stroma After the Inhibition of 5-Alpha Reductase and Aromatase in Gerbil Ventral Prostate - Corradi, Lara S. [UNESP]; Goes, Rejane M. [UNESP]; Vilamaior, Patricia S. L.; Taboga, Sebastiao R. [UNESP] (Wiley-liss, 2009)
Prostate require high levels of steroidogenic enzymes such as 5 alpha-reductase (5 alpha-r) and Aromatase (Aro) for the formation of active steroids. Dihydrotestosterone (DHT), the prostate dominant androgen, is converted from testosterone (T) by the action of 5 alpha-r. Aro provides an alternative pathway for estrogen, via T aromatization. Since prostatic maintenance is dependent on both reciprocal stromal-epithelial interaction and regulation by steroids, this study aimed to elucidate what the absence of 5 alpha-r and Aro enzymes provokes in the prostate microenvironment after their long-term inhibition. Data obtained 1 day after the 30 consecutive days of enzymatic inhibition with Finasteride (5 alpha-r inhibitor) and Letrozole (Aro inhibitor) demonstrated a marked stromal remodeling, with an increased deposition of extracellular matrix (ECM) proteins besides androgen receptor (AR) overexpression in the three phases of postnatal development analyzed. The subepithelial area of acini from ventral prostate presented collagen and reticular fibers accumulation, besides various altered and active fibroblasts. The AR content immunostaining was elevated after enzymatic inhibition therapy, mainly in the nuclei of epithelial cells. Similar data were observed in the ventral prostates even 21 days after the end of treatments. Results obtained following the long-term inhibition of 5 alpha-r and Aro are relevant and highlight the actions of these enzymes as crucial not only for the maintenance of tissue architecture and ECM arrangement but also for androgen and AR function. The long-term absence of their action imposes a novel situation on the prostate from which its normal physiology could not be restored by the conclusion of the treatments. Microsc. Res. Tech. 72:939-950, 2009. (C) 2009 Wiley-Liss, Inc.
Keywords: stromal reaction; androgen receptor; 5 alpha-reductase; aromatase; gerbil; ventral prostate